Chapter 1 Recentring, Reframing and Reimagining the Canons of Educational Research - Swartz, Sharlene (Taylor & Francis, 2024)
This chapter reviews the current canons of educational research and considers how they can be uncoupled from hegemonic knowledge paradigms which privilege Northern contexts. It outlines contributions from decolonial thinking and Southern theory and shows what must change if new epistemologies and ontologies are to emerge. It focuses on Southern epistemologies that illuminate ways of researching education in Southern contexts by students from the South researching their own contexts, and those trained in the North but researching Southern contexts. We consider critically the ways in which qualitative and quantitative research into structures, processes, and interactions have been challenged historically and the contemporary debates about whether, and if so how, such ethical and practical approaches can be transferred and be of value within Global South societies. Important insights are provided by experienced education researchers tackling the challenge of creating, identifying, or adapting research ethics, methods of data collection, and forms of data analysis.